Faktor-Faktor yang Berhubungan dengan Mortalitas pada Pasien Pediatrik yang Menjalani Pembiusan di Masa Pandemi Covid-19 di RSUP DR Sardjito - Djajantisari; Getar M, Geza Getar M; Widyastuti, Yunita (Jurnal Komplikasi Anestesi, 2023)
Background: Anesthesia has the potential to cause physiological changes that lead to morbidity and mortality. Perioperative mortality alone is higher in children than in adults. During this time, the COVID-19 pandemic has affected anesthesia care around the world. The practice of pediatric surgery shows a significant decrease in the frequency of elective surgeries during the pandemic compared to the last three months before the pandemic. Surgical delays that occur, especially in "time-sensitive" surgeries and urgent illnesses in children, can affect the child's growth, development, and quality of life. There are several risk factors associated with mortality and morbidity in pediatric patients, namely age, ASA III-V physical status, emergency surgery, use of ventilators, oxygen support, inotropic drug support, preoperative sepsis, and patients refusing resuscitation. Objective: Identifying factors that influence mortality in pediatric patients undergoing anesthesia during the COVID-19 pandemic. Method: This study is a retrospective cohort observational study. This study included all pediatric patients who underwent anesthesia at Dr. Sardjito General Hospital between April 1, 2020 - March 31, 2021. Variables suspected of having a relationship with mortality will be tested bivariately in this study, and if p<0.25 is considered significant, they will be included in the multivariate analysis. They will be excluded from the multivariate analysis if p<0.05 is considered significant. Result: Factors that influence the incidence of mortality in pediatric patients undergoing anesthesia at Dr. Sardjito General Hospital are ASA III-V physical status with a value of p = 0.004 (OR 3.47), and the use of mechanical ventilation postoperative with a value of p=<0.001 (OR 9.46), both factors that have a significant effect with a p<0.05. Conclusion: ASA III-V physical status and the use of mechanical ventilation postoperative are factors that significantly influence the mortality of pediatric patients undergoing anesthesia at Dr. Sardjito General Hospital.